From Suffering to Self-Realization: Spiritual Transformation in Hesse's Journey to the East - Bist, Resham Bahadur; Kandel, Rajan Kumar (The Outlook: Journal of English Studies, 2026)
Set against the backdrop of post-World War I Europe, marked by collective trauma, social fragmentation, and existential disorientation, Herman Hesse's novella Journey to the East (1932) portrays the quest for human spiritual restoration and inner transformation. In this context, this study examines the spiritual trajectory of the protagonist H.H. in the novella through the combined theoretical tool of Carl Jung's insight into individuation and Hindu- Buddhist soteriological concepts on suffering  and salvation. Within the dual theoretical frameworks, the analysis of the text reveals that suffering, ethical responsibility, and self-reflection help individuals to achieve psychological and spiritual  wholeness. H.H.'s experience of despair, fading memories, and psychological stagnation corresponds to the preliminary stages of a Jungian ego crisis. Simultaneously, these experiences mirror the Buddhist doctrine of Duhkha (existential suffering) and Hindu notions of Karma and Dharma. His suffering emerges from the Karmic consequences of deviating from his moral and spiritual duty to the League. Through H.H.'s relationship with Leo, a servant-leader who embodies both the Jungian wise old man archetype and the spiritual guide, H.H. confronts his psychological shadow, embraces selfless service, and moves toward self-realization. The study argues that Hesse portrays suffering or post-war trauma as a catalyst for spiritual realization and psychological wholeness rather than a terminal condition of defeat or despair, even in modern existential uncertainty and hardship.